2012
DOI: 10.4162/nrp.2012.6.3.201
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin ameliorates hyperglycemia and dyslipidemia and improves antioxidant status in type 2 diabetic db/db mice

Abstract: This study investigated the hypoglycemic, hypolipidemic, and antioxidant effects of dietary quercetin in an animal model of type 2 diabetes mellitus. Four-week-old C57BL/KsJ-db/db mice (n = 18) were offered an AIN-93G diet or a diet containing quercetin at 0.04% (low quercetin, LQE) or 0.08% of the diet (high quercetin, HQE) for 6 weeks after 1 week of adaptation. Plasma glucose, insulin, adiponectin, and lipid profiles, and lipid peroxidation of the liver were determined. Plasma glucose levels were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
149
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(173 citation statements)
references
References 39 publications
17
149
2
5
Order By: Relevance
“…The present results are in good accordance with other published studies carried out in animal models showing insulin resistance or type 2 diabetes (Wein et al 2010;Rivera et al 2008;Kim et al 2011;Jeong et al 2012). Nevertheless, there is no general agreement concerning the effect of quercetin on glycemic control.…”
Section: Controlsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results are in good accordance with other published studies carried out in animal models showing insulin resistance or type 2 diabetes (Wein et al 2010;Rivera et al 2008;Kim et al 2011;Jeong et al 2012). Nevertheless, there is no general agreement concerning the effect of quercetin on glycemic control.…”
Section: Controlsupporting
confidence: 91%
“…The authors of those studies which found positive effects of quercetin on glycemic control proposed several mechanisms to explain the beneficial effect of this polyphenol: (a) the anti-oxidative protective action on the pancreatic islets (Coskun et al 2005;Babujanarthanam et al 2010;Jeong et al 2012), (b) the increase in adiponectin circulating concentration (Wein et al 2010), (c) the inhibition of small intestine glucosidase activity , (d) the reduction in the intestinal glucose absorption mediated by GLUT2 (Kwon et al 2007), (e) the increase in glucokinase activity (Vessal et al 2003) and (f) the increase in GLUT4 transporters in skeletal muscle (Jung et al 2011;Shen et al 2012;Anhê et al 2012).…”
Section: Controlmentioning
confidence: 99%
“…A decrease of the glucose level in blood by 56.58% in the individuals with diabetes I and 71.61% in those suffering from diabetes II (Hatware and Annapurna, 2014) was noted. Jeong et al (2012) obtained interesting results, too. During their experiments they administered quercetin at 0.04 or 0.08% of the feed mass for 6 weeks to mice suffering from diabetes II.…”
Section: Antidiabetic Activitymentioning
confidence: 89%
“…However, no statistically significant differences were spotted between the animal groups to which various quercetin concentrations were administered. Moreover, statistically higher level of adiponectin -a protein released by adipose tissue and responsible for increasing the sensitivity of tissues to insulin (Jeong et al, 2012), was noted in individuals given 0.08% quercetin dose. Another experiment, with rats eating for 7 weeks feed containing 0.08% quercetin, observed a statistically significant decrease of glycated haemoglobin concentration, in respect to the investigated flavonoid addition deprived group.…”
Section: Antidiabetic Activitymentioning
confidence: 96%
See 1 more Smart Citation